Design and Optimization of Hybrid System for a Rural Based Light Industry and Domestic Load (International Journal of Innovative Research in Engineering & Management, 2022)
The most popular kind of energy is  electrical energy. Large power plants often create it, and  the national grid then distributes it to other areas. It is  obvious that India's supply of electrical energy is  inadequate because of some challenging geographic  features like terrain, mountains, and flood plains.  Additionally, power is typically of poor quality, and  outages happen frequently. Maintaining the household and  light industrial load in this situation is challenging. In this  study, wind energy is integrated with solar photovoltaic  (PV) technology. Due to the intermittent nature of both  sources, a battery bank with sufficient capacity has been  installed to ensure supply continuity. Simulated in  standalone mode is the system. The plan looks at various  pairings, assesses cost effectiveness, and studies pollutant  emission reduction. The plan attempts to recommend the  ideal size of the solar PV-wind integration and the system's  BoS, which will be able to deliver appropriate power  quality with improved reliability and a minimal levied cost  of energy.
Keywords: Hybrid System; Domestic Load; Solar Wind; Renewable